Assessment of Nutritional Status of Hospitalized Elderly Patients in Makkah Governorate - Elmadbouly, Muhammad A.; Elhafez, Amany M. Abd (Pakistan Journal of Nutrition, 2012)
A cross sectional study was conducted to assess the nutritional status of a sample of 102 recently hospitalized elderly patients in general hospitals at Makkah Governorate by using the Mini Nutritional Assessment (MNA) tool. Among the studied patients, 22.6% were classified as malnourished, 57.8% were at risk of malnutrition and 19.6% were as well nourished. Low body mass index, history of weight loss during the last 3 months, living independently, taking > 3 prescription of drugs per day and presence of neuropsychological problems were associated with malnutrition (p